Gender Transformative-Socio-Technical Innovation Bundles (GT-STIBs): A tool in the CGIAR Gender Transformative Research Methodologies (GTRM) toolkit - Nchanji, Eileen; Ketema, Dessalegn; Lutomia, Cosmas (2025)
Tool 3 in the Gender Transformative Research Methodologies Toolkit. The Gender-Transformative Socio-Technical Innovation Bundling (GT-STIBs) tool helps researchers, extension actors, private sector partners, local and international partners co-design and test innovation packages that deliberately and systematically combine technological, technical, social, and institutional components to shift harmful gender norms and expand women’s and youth’s agency in agrifood systems. They also build individual and community resilience, food security, with women and youth as drivers of change. Operates at all levels from individual to macro.